Analisis Permintaan Telur Ayam di Kabupaten Magetan - Nia Fridayanti; Siti Marwanti; Ernoiz Antriyandarti (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2018)
This research aims to identify and to analyze the variables which influenced the chicken egg demand in Magetan District and to know its elasticity. This research used descriptive and analytical method. The research location was chosen purposively in Magetan. By using 27 years time series data, this study applied Cobb Douglass demand functing with OLS method. The results showed that the price of chicken egg race, chicken meat price, rice price, population and income per capita have significant effect on chicken egg demand in Magetan District. Race egg price has inelastic elasticity since its value is negative (-0,280). Chicken meat price has subtitute elasticity since its value is positive (0,911). Rice price has complementary elasticity since its value is negative (-0,233). Income elasticity has a negative (-0,476) value means that chicken egg is an inferior good for Magetan District.